Emotion Regulation in Schema Therapy and Dialectical Behavior Therapy - Fassbinder, Eva; Schweiger, Ulrich; Martius, Desiree; Brand-de Wilde, Odette; Arntz, Arnoud (Frontiers in Psychology, 2016)
Schema therapy (ST) and dialectical behavior therapy (DBT) have both shown to be effective treatment methods especially for borderline personality disorder. Both, ST and DBT, have their roots in cognitive behavioral therapy and aim at helping patient to deal with emotional dysregulation. However, there are major differences in the terminology, explanatory models and techniques used in the both methods. This article gives an overview of the major therapeutic techniques used in ST and DBT with respect to emotion regulation and systematically puts them in the context of James Gross’ process model of emotion regulation. Similarities and differences of the two methods are highlighted and illustrated with a case example. A core difference of the two approaches is that DBT directly focusses on the acquisition of emotion regulation skills, whereas ST does seldom address emotion regulation directly. All DBT-modules (mindfulness, distress tolerance, emotion regulation, interpersonal effectiveness) are intended to improve emotion regulation skills and patients are encouraged to train these skills on a regular basis. DBT assumes that improved skills and skills use will result in better emotion regulation. In ST problems in emotion regulation are seen as a consequence of adverse early experiences (e.g. lack of safe attachment, childhood abuse or emotional neglect). These negative experiences have led to unprocessed psychological traumas and fear of emotions and result in attempts to avoid emotions and dysfunctional meta-cognitive schemas about the meaning of emotions. ST assumes that when these underlying problems are addressed, emotion regulation improves. Major ST techniques for trauma processing, emotional avoidance and dysregulation are limited reparenting, empathic confrontation and experiential techniques like chair dialogues and imagery rescripting.